Effect of 8-Week of Selected Aerobic Exercise on Static and Dynamic Balance in Healthy Elderly Inactive Men - Mirmoezzi, Masoud; Amini, Mojtaba; Khaledan, Asghar; Khorshidi, Davood (Sālmand. (Tihrān), 2016)
Objectives: Old age refers to years near or passed the middle age and therefore, near to the end of lifecycle. Old-aged people have limited reviving capability and are more at risk of catching diseases, syndromes,and ailments. Falling is one of the most common problems in the elderly that occur due to theirinability to maintain balance. This study aimed to examine the effect of aerobic exercises on static anddynamic balance in healthy elderly inactive men. Methods & Materials:This quasi-experimental research was done in older people living in a nursing homein Qazvin, Iran. The study population included 200 elderly men (65-75 years old); of them, 26 healthy,inactive men were randomly selected and assigned to the experimental (13 subjects) and control (13subjects) groups. The experimental group participated in selected exercise programs for 8 weeks. Weused personal information questionnaire to check the inclusion criteria that comprised independency indoing daily chores, lack of problems in vision or fall during the last year, and not having joints dislocation,chronic arthritis or vertigo. In the case of having these problems, the subjects were excluded from thestudy. Stork balance test and Timed Up and Go test were used to measure the static and dynamic balanceof subjects before the initiation and after the termination of the program. The statistical analyseswere done by paired and independent t-tests. Results: The results of independent t-test did not indicate any significant differences between 2 groupswith regard to age, height, and weight (P>0.05). Homogeneity was observed in the 2 groups with respectto individual features affecting balance and walking. After performing the aerobic exercise program, thedynamic balance in the experimental group increased significantly (P<0.001). In the dynamic balancetest, the lower mean time supported the better execution of the test, and significant changes wereobserved in the experimental group. The comparison of the two groups indicated the positive effect of aerobic exercise on the dynamic balance of healthy older people; however, no significant change wasseen in static balance (P=0.36). Since we used Stork test for determining static balance, the higher meantime supported the positive effect but with no significant change in the static balance of experimentalgroup after 8 weeks. We found that different factors like lower extremity muscles such as soleus, gastrocnemius,and hamstring have some roles in keeping static balance, and as the exercise protocol wasrelated to aerobic exercise (walking and jogging), it did not reinforce these muscles. Conclusion: Our results showed that regular aerobic exercise improves dynamic balance in elderly men.We also found that jogging and walking improved dynamic balance. The improvement in balance may bedue to the increase in nervous compatibility (due to exercise); increase in fitness, strength, and motiondomain; improvement in aerobic status, response time and mental status; improvement in neuromuscularcontrol, including a decrease in changing movement units; and improvement in simultaneous movementunits. Furthermore, there is a positive relationship between body composition and movementwith balance. Therefore, regular aerobic activities are recommended as a suitable training method forimproving balance.